ANALISIS KINERJA KEUANGAN PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2020 – 2022 - Aiedil Pebri Suwarna; Abd Azis Muthalib; Muh Nur (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This study aims to analyze the financial performance of banks listed on the Indonesia Stock Exchange, focusing on PT. Bank Rakyat Indonesia (BRI) and PT. Bank Mandiri for the period 2020-2022. The method used is financial ratio analysis, including activity ratios, profitability ratios, liquidity ratios, and solvency ratios. The analyzed data shows that the financial performance of both banks in terms of activity ratios has not reached an efficient and effective level. However, in terms of profitability ratios, both banks show good performance with the ability to generate above-average profits. On the other hand, the liquidity and solvency ratios of both banks are below average, indicating a lack of ability to meet short-term and long-term obligations. This study uses a purposive sampling approach, based on specific criteria that have been established. The results of the study provide insights regarding the importance of managing financial ratios to improve the financial performance of banking in Indonesia.